Monitoring high thermal performance concrete for concentrated solar power plants with fibre optic sensors - Ruiz-Lombera, Rubén; Grandal, Tania; Fraga, Sergio (SIMAR 2019 - Fifth Conference on Smart Monitoring, Assessment and Rehabilitation of Civil Structures, 2019)
In this paper a monitoring system for concrete structures at high temperatures (500ºC) is presented. The aim of the monitoring strategy based on fibre optic sensors (FOS) is to develop a high-tech monitoring technology for future installation in Concentrated Solar Power (CSP) plants with the purpose of lifecycle analysis and predictive maintenance via structural health monitoring (SHM). The monitoring strategy is based on embedding FOS in high thermal performance concrete while it is casting. The FOS technology employed to monitor both temperature and strain in concrete is known as Fibre Bragg Grating (FBG). In this work, the development of the special metallic coating and smart packaging employed to protect the sensors in this harsh environment, the calibration of the sensors and the thermal validation of the monitoring system at lab scale working in a range of temperatures between 200ºC and 500ºC is demonstrated. The lab tests were performed over a sample of 30x30x30cm, composed of 2 different layers and 4 tubes of steel, the core is made with concrete specially manufactured to have a very good thermal behaviour, and the second layer is for the insulating, and it is formed by foam concrete. The FBG sensors were positioned longitudinally, parallel to the tubes by drill holes on the casting structure at 14 different positions. The concrete curing process and some different heating cycles up to 500ºC, simulating the thermal behaviour of CSP plants, were monitored using the fibre sensors
Keywords: Monitoring; Concrete; Concentrated Solar Power; Thermal performance; fibre optics